Question
upstudy study bank question image url

A function is given. \( f(x)=5-3 x^{2} ; \quad x=4, x=4+h \) (a) Determine the net change between the given values of the variable. (b) Determine the average rate of change between the given values of the variable. (b)

Ask by Ford Santiago. in the United States
Jan 31,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

**(a) Net Change:** \( -24h - 3h^2 \) **(b) Average Rate of Change:** \( -24 - 3h \)

Solution

Let's address each part of the problem step by step. Given the function: \[ f(x) = 5 - 3x^{2} \] and the two values of \( x \): \[ x = 4 \quad \text{and} \quad x = 4 + h \] --- ### **(a) Net Change Between the Given Values of the Variable** **Net change** refers to the difference in the function's value when the input changes from \( x = 4 \) to \( x = 4 + h \). Mathematically, it's expressed as: \[ \text{Net Change} = f(4 + h) - f(4) \] **Step-by-Step Calculation:** 1. **Calculate \( f(4) \):** \[ f(4) = 5 - 3(4)^2 = 5 - 3(16) = 5 - 48 = -43 \] 2. **Calculate \( f(4 + h) \):** \[ f(4 + h) = 5 - 3(4 + h)^2 \] First, expand \( (4 + h)^2 \): \[ (4 + h)^2 = 16 + 8h + h^2 \] Then substitute back: \[ f(4 + h) = 5 - 3(16 + 8h + h^2) = 5 - 48 - 24h - 3h^2 = -43 - 24h - 3h^2 \] 3. **Determine Net Change:** \[ \text{Net Change} = f(4 + h) - f(4) = (-43 - 24h - 3h^2) - (-43) = -24h - 3h^2 \] **Answer for Part (a):** \[ \text{Net Change} = -24h - 3h^2 \] --- ### **(b) Average Rate of Change Between the Given Values of the Variable** The **average rate of change** of the function between \( x = 4 \) and \( x = 4 + h \) is given by: \[ \text{Average Rate of Change} = \frac{f(4 + h) - f(4)}{h} \] Using the net change from part (a): \[ \text{Average Rate of Change} = \frac{-24h - 3h^2}{h} \] **Simplify the Expression:** \[ \text{Average Rate of Change} = -24 - 3h \] **Answer for Part (b):** \[ \text{Average Rate of Change} = -24 - 3h \] --- ### **Summary** - **(a)** The net change is \( -24h - 3h^2 \). - **(b)** The average rate of change is \( -24 - 3h \).

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Mind Expander

To find the net change of the function \( f(x) = 5 - 3x^2 \) between \( x = 4 \) and \( x = 4 + h \): (a) First, we calculate \( f(4) \) and \( f(4 + h) \): - \( f(4) = 5 - 3(4^2) = 5 - 48 = -43 \) - \( f(4 + h) = 5 - 3(4 + h)^2 = 5 - 3(16 + 8h + h^2) = 5 - 48 - 24h - 3h^2 = -43 - 24h - 3h^2 \) Now, the net change is: \[ \Delta f = f(4 + h) - f(4) = (-43 - 24h - 3h^2) - (-43) = -24h - 3h^2 \] (b) The average rate of change between \( x = 4 \) and \( x = 4 + h \) is given by: \[ \text{Average Rate of Change} = \frac{f(4 + h) - f(4)}{(4 + h) - 4} = \frac{-24h - 3h^2}{h} = -24 - 3h \] So, the answers are: (a) The net change is \( -24h - 3h^2 \). (b) The average rate of change is \( -24 - 3h \).

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy